Modal dispersion curves of an optical fiber with a trefoil cross-section under the weak guidance approximation - Sharma A.; Khastgir P.; Singh O.N. (My University, 2025)
We consider the dispersion curves for some lower order modes sustained by a fiber whose guiding region has a trefoil-like cross-section. Such a fiber resembles a multicore structure in which three cores are embedded in a common cladding. From the characteristic equation obtained under the weak guidance approximation, the dispersion curves are obtained and interpreted.